Five years of ReCLes.pt: building a national network in Higher Education - Arau Ribeiro, María Del Carmen (2021)
ReCLes. pt 2014 International Conference on Languages and the Market: Competitiveness and Employability, Escola Superior de Hotelaria e Tourismo de Estoril, Estoril, Portugal